A Communication Strategy for Promoting Halal Beauty Products: An Analysis of Syntactic Features - Rizky Vita Losi; Rosida, Sisi; Nasution, Muhammad Muslim; Rahayu, Yoni (Proceedings of International Conference on Da'wa and Communication, 2023)
Language is the most important component for a successful advertising products. This study aimed to analyze the language used of slogans in online advertisement which taken from halal beauty products based on the syntactic features. This study used descriptive qualitative as the research design and textual analysis was used to analyze the data. There were 61 data which were taken from the slogans of Wardah product advertisement. Based on the data analysis, it was found that there were short sentence (1 data), long-noun phrase (19 data), ambiguity (3 data), use of imperative (25 data), simple and colloquial language (1 data), use of present tense (1 data), syntactic parallelism (3 data), association (4 data), ellipsis (2 data), and incomplete sentence (2 data). The findings on the use of imperative became the most used feature in the slogans. The advertisement used imperative to persuade the consumers directly to follow the directions or instructions made in Wardah slogans.